Sports performance judgments from a social cognitive perspective - Plessner, Henning; Haar, Thomas (Psychology of sport and exercise, 2006)
Objective - Judging one's own or others’ performance is a central task for most people involved in competitive sports—either as athletes, coaches, referees, or spectators. Social cognition is the general study of how people make sense of other people and themselves on the basis of an information processing framework. This paper presents a social-cognitive overview of empirical work on judging sport performance. It follows the basic steps of social information processing (i.e., perception, encoding/categorization, memory processes, and information integration). - Conclusions - Ample anecdotal and empirical evidence indicates that sports performance judgments are at least as prone to systematic errors (biases) as other social judgments. Thus, achieving accurate performance evaluations can help to improve the quality of decision making on various levels of sport behavior (e.g., referee decisions, strategy choice, team selection). The application of a social cognition approach provides insights into the processes that underlie biases in judgments of sport performance and, thus, some hints on how to prevent them. In addition, we propose possible future applications of social cognition concepts in sports judgment research.
Available online 8 June 2006
Gesehen am 22.07.2022